Investigation of Virulence and Cytolethal Distending Toxin Genes in Campylobacter spp. Isolated from Sheep in Turkey - Acik, Mehmet N.; Karahan, Murat; Ongor, Hasan; Cetinkaya, Burhan (Mary Ann Liebert Inc, 2013)
The presence of virulence and cytolethal distending toxin (Cdt) genes was investigated in isolates of Campylobacter jejuni, C. coli, C. lanienae, and C. lari that originated from intestinal contents and gallbladders of clinically healthy sheep. These genes have important roles in the pathogenicity of campylobacters. A total of 363 Campylobacter isolates (221 C. jejuni, 135 C. coli, five C. lanienae, and two C. lari) were used in this study. The frequency of racR, dnaJ, ciaB, pldA, flaA, and cadF virulence genes in all the isolates were determined to be 34.4%, 30%, 24.8%, 30.9%, 95%, and 81.3%, respectively, while the virB11 virulence gene could not be detected in any isolates. CdtA, cdtB, and cdtC genes were detected in 54.5%, 55.9%, and 52.3% of the isolates, respectively. None of the virulence and toxin genes examined here were detected in a total of 19 Campylobacter isolates consisting of 10 C. jejuni and nine C. coli. This is the first study investigating the presence of virulence and toxin genes in a large number of Campylobacter species isolated from clinically healthy sheep by scanning a large area. In addition, this is the first report investigating the presence of virulence and toxin genes in sheep-originated C. lanienae and C. lari isolates.
Keywords: Pcr Detection; Jejuni Strains; Coli; Prevalence; Identification; Cattle; Cells; Cdtb; Colonization; Invasion